Point cloud resampling using centroidal Voronoi tessellation methods. (September 2018) - Chen, Zhonggui; Zhang, Tieyi; Cao, Juan; Zhang, Yongjie Jessica; Wang, Cheng
Abstract: This paper presents a novel technique for resampling point clouds of a smooth surface. The key contribution of this paper is the generalization of centroidal Voronoi tessellation (CVT) to point cloud datasets to make point resampling practical and efficient. In particular, the CVT on a point cloud is efficiently computed by restricting the Voronoi cells to the underlying surface, which is locally approximated by a set of best-fitting planes. We also develop an efficient method to progressively improve the resampling quality by interleaving optimization of resampling points and update of the fitting planes. Our versatile framework is capable of generating high-quality resampling results with isotropic or anisotropic distributions from a given point cloud. We conduct extensive experiments to demonstrate the efficacy and robustness of our resampling method. Graphical abstract: Highlights: A versatile framework for uniform/adaptive or isotropic/anisotropic point resampling. It is able to remove noise and fill holes or preserve boundaries of the point cloud. The resampling quality is not affected by the distribution of the input point cloud. The running time is mainly determined by the number of resampling points.